2020
DOI: 10.1111/and.13511
|View full text |Cite
|
Sign up to set email alerts
|

Human spermatozoa of male patients with subfertility express the interleukin‐6 receptor

Abstract: Male subfertility has been associated with bacterial infections and chronic inflammation. In this context, several studies investigated cytokine levels in seminal plasma, whereas interleukin‐6 (IL‐6) appears to be crucial. However, little is known about its receptor, the IL‐6R expression on human spermatozoa. Thus, the aim of the present study was to screen spermatozoa for IL‐6R expression and to identify its localisation. Semen samples of 137 patients (median age 37.69, SD ± 7.82) with subfertility were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 35 publications
0
3
0
2
Order By: Relevance
“…Proteins are very important for the biological process of the sperms. Many studies have demonstrated that proteins have effects on the biological functions of sperm, such as motility, capacitation, acrosome reaction, and fertilization (Djourabchi Borojerdi et al, 2020;Wu et al, 2020). In fish species, there was no report about the effects of storage in vitro on transcriptome and proteome levels.…”
Section: Introductionmentioning
confidence: 99%
“…Proteins are very important for the biological process of the sperms. Many studies have demonstrated that proteins have effects on the biological functions of sperm, such as motility, capacitation, acrosome reaction, and fertilization (Djourabchi Borojerdi et al, 2020;Wu et al, 2020). In fish species, there was no report about the effects of storage in vitro on transcriptome and proteome levels.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, inflammatory cytokines recruit and activate leukocytes, which results in increased ROS production 29 . Previous studies have reported that sperm quality was decreased, especially low sperm motility, after incubation of spermatozoa with several cytokines, including IL‐6, TNF‐α, IFN‐γ, IL‐17A, and IL‐1β 30–32 . Thus, inflammatory cytokines released by leukocytes may lead to an inflammatory response resulting in poor semen quality.…”
Section: Discussionmentioning
confidence: 99%
“…Increased seminal levels of inflammatory cytokines are considered to be resultant of the so-called cytokine storm, a phenomenon usually presented by patients with COVID-19 [ 54 ], which may induce harmful side effects in the testis and epididymis through the stimulation of local inflammation and oxidative stress. It is well known that inflammatory cytokines, in particular IL-6, TNF, and IL-1β, and oxidative stress are deleterious to spermatogonia and spermatozoa as they trigger deregulated ROS production and elicit apoptosis [ [11] , [55] , [56] , [57] , [58] ]. In addition, a negative correlation has been demonstrated between seminal IL-1β and TNF concentrations and sperm concentration and total sperm count in SARS-CoV-2 infected patients, with the highest IL-1β levels detected in the group of patients with crypto-azoospermia [ 37 ].…”
Section: Discussionmentioning
confidence: 99%